Studi Trend Ibadah Dalam Nyanyian dan Musik Kontemporer di Gereja-gereja Baptis Masa Kini - Lumbantobing, Tomson Saut Parulian; Suseno, Aji (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
The decision of several Baptist churches to start using contemporary singing and music in the early 2000s has caused controversy and has become a polemic in the Association of Indonesian Baptist Churches (GGBI). However, the trend of worship using contemporary songs and music is getting more widespread in Indonesian Baptist churches. This is the background of this research, which is to comprehensively investigate the factors behind the widespread trend of worship using contemporary songs and music in Indonesian Baptist churches. Thus, the formulation of the research problem is a study of the factors behind the widespread trend of worship using contemporary songs and music in Indonesian Baptist churches. This type of research is classified as a descriptive qualitative variety with a literature study. Data were obtained from various document sources such as books, magazines, articles, and scientific journals about worship, spiritual songs, and music. The results of the research found that the congregational government system, church planting, seminars and writings on worship and music, Baptist youth worship, and technological developments are factors behind the increasingly widespread trend of worship with contemporary singing and music in Indonesian Baptist churches.AbstrakKeputusan beberapa gereja Baptis yang mulai menggunakan nyanyian dan musik kontemporer di awal tahun 2000an telah menimbulkan kontroversi dan menjadi polemik di Gabungan Gereja-Gereja Baptis Indonesia (GGBI). Meskipun demikian, trend ibadah menggunakan nyanyian dan musik kontemporer justru semakin meluas di gereja-gereja Baptis Indonesia. Hal inlah yang melatarbelakangi dilakukannya riset ini, yaitu hendak menyelidiki secara komprehensif faktor-faktor yang melatarbelakangi semakin meluasnya trend ibadah menggunakan nyanyian dan musik kontemporer di gereja-gereja Baptis Indonesia. Dengan demikian, rumusan masalah riset ini adalah kajian tentang faktor-faktor yang melatarbelakangi semakin meluasnya trend ibadah menggunakan nyanyian dan musik kontemporer di gereja-gereja Baptis Indonesia. Jenis riset tergolong dalam ragam kualitatif deskriptif dengan studi literatur. Data diperoleh dari berbagai sumber dokumen seperti seperti buku, majalah, artikel dan jurnal-jurnal ilmiah tentang ibadah, nyanyian dan musik rohani. Hasil riset menemukan bahwa sistem pemerintahan kongregasional, perintisan jemaat, seminar dan karya tulisan tentang ibadah dan musik, ibadah kaum muda Baptis, serta perkembangan teknologi merupakan faktor-faktor yang melatarbelakangi semakin meluasnya trend ibadah dengan nyanyian dan musik kontemporer di gereja-gereja Baptis Indonesia.